Linear blind channel equalization for GSM systems - Ding, Zhi; Ge Li (1998 IEEE International Conference on Communications, 1998)
We focus on the design of blind equalization receiver for the phase modulated GSM systems without relying on additional antennas. We derive an equivalent baseband PAM model for the GMSK signal used in GSM systems. More importantly, we are able to use a de-rotation scheme to create two sub-channels for each GMSK signal even though the GMSK signal has almost zero excess bandwidth. The significance of the first discovery is that traditional QAM blind equalization algorithms can now be applied to GSM systems. The significance of the second discovery reduces the necessary RF receivers (sensors) by half without increasing any additional hardware or computational costs. Simulation results are presented for several second order statistical (SOS) and high order statistical (HOS) methods.